The Effect of High-Intensity Interval Training (HIIT) in Increasing Endurance and Preventing Injuries in Football Players - Sandi, Kurnia; Fedora, Feren; Komarudin, Komarudin; Hermawan, Hedi Ardiyanto (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
This study aims to evaluate the effect of High-Intensity Interval Training (HIIT) on improving physical endurance performance and reducing the risk of injury in football players. This study utilizes a quasi-experimental design with a one-group pre-test and post-test approach involving 20 football players aged 18 to 25. Resistance performance is measured through VO₂ Max, while injury risk is assessed using body functional tests that evaluate muscle imbalances and biomechanical weakness. After undergoing the HIIT program for 8 weeks, the results showed a significant improvement in the players' VO₂ Max from an average of 61.87 ± 6.03 ml/kg/min to 63.60 ± 6.03 ml/kg/min, with an increase of 2.8% (p < 0.05). In addition, the risk of injury also decreased from an average of 4.11 ± 0.86 to 4.07 ± 0.86, with a decrease of 1.1% which was also statistically significant (p < 0.05). The increase in VO₂ Max reflects the increase in the player's cardiovascular endurance, which is crucial for dealing with the physical demands of a football match. The research also reveals that the reduced risk of injury suggests that HIIT effectively improves muscle stability, flexibility, and balance, which are important in preventing muscle and joint injuries in football players. In conclusion, HIIT is an efficient and effective training method to improve physical performance and reduce the risk of injury, so it is recommended to be applied in the training program of football players